Beat the odds in forex trading : how to identify and profit from high percentage market patterns - Toshchakov, Igor (Hoboken, N.J. : John Wiley & Sons, 2006)
Beat the Odds in Forex Trading presents a practical approach that adds certainty and systematization into Forex trading. Author and industry professional Igor Toshchakov shows how recurring market patterns----which can be recognized on a simple bar chart----can be successfully used to trade the Forex market.
Includes index.
oif 31/08/2015
Loan
Keywords: Foreign exchange market; Foreign exchange futures; Speculation